Computer Based Body Exposure in Adolescents With Anorexia Nervosa: A Study Protocol - Stonawski, Valeska; Sasse, Lena; Moll, Gunther; Kratz, Oliver; Horndasch, Stefanie (Frontiers in Psychiatry, 2022)
Body dissatisfaction is a core feature of eating disorders (EDs) and plays an essential role in the development and maintenance of anorexia nervosa (AN). In the current study, a computer based body exposure intervention is conducted and evaluated regarding short-term effects on body dissatisfaction, psychopathology, viewing patterns, and stress reactivity. Within a randomized controlled trial (RCT) female adolescents and young women with AN are either receiving the intervention or treatment as usual (TAU). Furthermore, in a transdiagnostic approach, a highly body-dissatisfied group of clinical control participants obtaining the intervention will be surveyed to identify AN-specific processes. The standardized four-session body exposure intervention using photographs of the own body is adapted from a manualized body image treatment program for computer use. Psychopathology (body dissatisfaction, body image avoidance, body checking, depression, anxiety) is assessed via standardized questionnaires before and after the intervention. During each session, attentional biases regarding one's own body are measured via eye tracking, stress levels are measured via subjective ratings, heart rate variability, as well as salivary cortisol and alpha amylase. Between- and within-subject effects will be assessed. The pilot study aims to identify short-term effects of the intervention on body dissatisfaction and attentional bias, as well as to investigate the potential underlying mechanism of physiological habituation.
CRIS-Team WoS Importer:2022-02-18

Evaluating a computer-based body exposure paradigm for the treatment of body image disturbance in adolescent Anorexia Nervosa: effects on the attentional bias and emotions. - Sasse, Lena; Stonawski, Valeska; Kratz, Oliver; Moll, Gunther; Horndasch, Stefanie (Frontiers in Psychology, 2024)
BACKGROUND: A diagnostic criterion of Anorexia Nervosa (AN) is body image disturbance. Body exposure therapy is a widely used approach to treat this; however, it is unclear which part of body exposure therapy is relevant for regaining a realistic perspective on the own body. This study aimed to examine the role of the attentional bias (AB), which AN patients exhibit to the most disliked parts of their body. Additionally, emotional responses to the body exposure sessions were examined. METHODS: Participants were adolescent girls with a diagnosis of AN, who were randomly assigned to either an intervention (INT) or a treatment-as-usual (TAU) group. Both groups completed a pre and a post session, which included the completion of questionnaires to measure AN-psychopathology. The INT group received four sessions of a computer-based body exposure between the pre and the post session. The viewing pattern was recorded before and after each intervention session via an eyetracking (ET) device, as were emotional response scores on a visual analog scale (VAS; anxiety and disgust). The TAU group did not receive the intervention, but viewing patterns were recorded during the pre and the post session. All participants were asked to list their three least favorite body parts to be able to subsequently assess the AB. RESULTS: Fifty-eight adolescent girls with AN participated in the study. There were no differences in psychopathology pre to post session, as measured by administered questionnaires. The existence of an AB could be replicated, but there was no significant reduction in the AB pre to post session in the INT group, nor was there an interaction between group and time. Also, no changes in the AB were found within and between sessions in the INT group. Anxiety scores reduced significantly across sessions while disgust scores were significantly higher post session than they were pre session. CONCLUSIONS: While the existence of an AB was demonstrated, the carried-out body exposures were neither sufficient to reduce the AB nor the psychopathology; nevertheless, a significant decrease in anxiety levels showed the usefulness of the exposure sessions. Future research might benefit from more exposure sessions and incorporating AB modification training (ABMT).
EVALuna2:578467